Modeling Malaysian Road Accidents: The Structural Time Series Approach - Junus, Noor Wahida Binti Md (2018)
Modeling the number of road accidents occurrence is a quite common topic in recent years. A number of studies have been developed with the aim to find the best model that gives better prediction. However, statistical patterns such as trend and seasonality of road accidents is rarely observed. Estimating the pattern of trend and seasonal will indirectly provide a better impact on prediction system. Traditionally, estimation of trend and seasonal patterns are made based on decomposition method. Yet, this type of estimation shows intangible predictions as the estimation are based on deterministic form. Therefore, structural time series (STS) approach is proposed to model the trend and seasonal pattern of road accidents occurrence. In this thesis the road accidents model is developed using the STS approach with the aim to observe the pattern of trend and seasonality of road accidents occurrence. This thesis was done on all 5 main regions and 14 states in Malaysia. The study further enhance investigation on road accidents influences at different locations with appropriate explanatory variables.